Cavernous hemangiomas - (:unkn) unknown (AMER ASSOC NEUROLOGICAL SURGEONS, 2005)
Extraaxial cavernous hemangiomas are rare intracranial lesions that can be located in different cranial compartments. Extension across different tissue planes such as the subcutaneous tissue, skull, orbital cavity, intracranial dura mater, and extracranial trigeminal divisions within the same patient has not been previously reported. This 32-year-old woman suffered left exophthalmos, left sixth nerve palsy. and trigeminal neuropathy. Magnetic resonance imaging Studies revealed an extensive multicompartmental lesion, with enhancement following Gd administration. A left orbitopterional approach allowed removal of several cavernomatous lesions located in the orbit, frontotemporal dura, and lateral wall of the cavernous sinus. A histologically based diagnosis of extraaxial cavernous hemangioma was made. In the postoperative period the patient experienced a regression of her symptoms. The authors report on a case of cavernous hemangioma with a unique extension to different intracranial/extracranial compartments. Although radical removal of the lesion was not feasible, partial excision allowed for satisfactory clinical control of the patient's symptoms.
Keywords: GAMMA-KNIFE RADIOSURGERY; SINUS